API5 confers tumoral immune escape through FGF2-dependent cell survival pathway - Noh, Kyung Hee (Cancer Res, 2014)
Identifying immune escape mechanisms used by tumors may define strategies to sensitize them to immunotherapies to which they are otherwise resistant. In this study, we show that the anti-apoptotic gene API5 acts as an immune escape gene in tumors by rendering them resistant to apoptosis triggered by tumor antigen-specific T cells. Its RNAi-mediated silencing in tumor cells expressing high levels of API5 restored antigen-specific immune sensitivity. Conversely, introducing API5 into API5(low) cells conferred immune resistance. Mechanistic investigations revealed that API5 mediated resistance by upregulating FGF2 signaling through a FGFR1/PKCδ/ERK effector pathway that triggered degradation of the pro-apoptotic molecule BIM. Blockade of FGF2, PKCδ or ERK phenocopied the effect of API5 silencing in tumor cells expressing high levels of API5, to either murine or human antigen-specific T cells. Our results identify a novel mechanism of immune escape that can be inhibited to potentiate the efficacy of targeted active immunotherapies.